2011
DOI: 10.3727/096368910x564067
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Derivation and Concise Gene Expression Profiling of Human Embryonic Stem Cell-Derived Mesenchymal Progenitors (EMPs)

Abstract: New potential sources of stem cells for clinical application include bone marrow mesenchymal stem cells (BMMSCs), human embryonic stem cells (hESCs), and induced pluripotent stem cells (iPS). However, each source is not without its own concerns. While research continues in an effort to overcome these problems, the generation of mesenchymal progenitors from existing hESC lines may circumvent many of these issues. We report here a simple and efficient method of generating hESC-derived mesenchymal progenitors (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 63 publications
3
66
0
Order By: Relevance
“…[10,39] on the basis of experiments showing that these PSC derivatives satisfied the minimal MSC criteria put forth by the ISCT [22,23]. On the other hand, recent published studies based on gene expression data [10,15,40] and in vitro differentiation assays [29,39,[41][42][43] 1604 DIEDERICHS AND TUAN suggested differences between BMSCs and MSC-like PSC derivatives. However, when interpreting these studies, it should be taken into consideration that the MSCs and ESCs originated from different donors.…”
Section: Gene Expression In Differentiated Impcs Compared To Bmscsmentioning
confidence: 99%
“…[10,39] on the basis of experiments showing that these PSC derivatives satisfied the minimal MSC criteria put forth by the ISCT [22,23]. On the other hand, recent published studies based on gene expression data [10,15,40] and in vitro differentiation assays [29,39,[41][42][43] 1604 DIEDERICHS AND TUAN suggested differences between BMSCs and MSC-like PSC derivatives. However, when interpreting these studies, it should be taken into consideration that the MSCs and ESCs originated from different donors.…”
Section: Gene Expression In Differentiated Impcs Compared To Bmscsmentioning
confidence: 99%
“…Repeated passaging by trypsinization has been showed to enriched MSCs population 28) . But, mechanism of why functional MSCs, or mesenchymal progenitor cells named by Yen et al in their study, can efficiently derived from iPSCs by serial culturing and trypsinization needs further investigations 29) . Zou et al showed one possibility, it might be associated with the used serum, but speculated that the serum effect should not be main effector 26) .…”
Section: Discussionmentioning
confidence: 99%
“…S1; Supplementary Data are available online at www.liebertpub.com/scd) [9,11,21,22,29,30]. The ability of hDE-MSCs to differentiate into various myogenic lineages, however, has not been investigated.…”
Section: Hde-mscs Poorly Differentiate Toward a Cardiomyocytic Phenotypementioning
confidence: 99%
“…hDE-MSCs, as a type of MSCs, are capable of multilineage differentiation [9,11,21,22,29,30], and we sought to ascertain the specificity of MM-induced SkM differentiation in these MSCs by assaying for changes in the levels of Runx2 and PPAR-c, the master lineage transcription factors for osteogenesis and adipogenesis, respectively [40,41]. We found that in all types of hDEMSCs undergoing SkM differentiation, the expression levels of Runx2 and PPAR-c are decreased compared with undifferentiated hDE-MSCs (Supplementary Fig.…”
Section: Skm Differentiation Of Hde-mscs Was Associated With Suppressmentioning
confidence: 99%
See 1 more Smart Citation